Writer Motivation: Beyond the Intrinsic/ Extrinsic Dichotomy - Bradford A. Barry (Journal of the Assembly for Expanded Perspectives on Learning, 1999)
This article articulates and develops a much needed theory of communication motivation which shows how we can nurture in our students rhetorically-based intrinsic motivations.